1963
DOI: 10.1086/626879
|View full text |Cite
|
Sign up to set email alerts
|

A Geochemical Study of Lakes Bonney and Vanda, Victoria Land, Antarctica

Abstract: dioxide fixation in marine invertebrates. I. The main pathway in the oyster: Jour. Biochemistry, v. 234, p. 1268.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
1

Year Published

1964
1964
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(38 citation statements)
references
References 7 publications
1
36
1
Order By: Relevance
“…2) and chemical analyses by Angino and Armitage ( 1963)) it is clear that the ice on both lakes was fresh. Accordingly, all calculations concerning thermal properties are based on values for freshwater ice.…”
Section: Rudiutionmentioning
confidence: 91%
See 1 more Smart Citation
“…2) and chemical analyses by Angino and Armitage ( 1963)) it is clear that the ice on both lakes was fresh. Accordingly, all calculations concerning thermal properties are based on values for freshwater ice.…”
Section: Rudiutionmentioning
confidence: 91%
“…Two of these, Lakes Bonney and Vanda, have received considerable attention from biologists and geologists (Armitagc and House 1962;Angino and Armitage 1963;Wilson and Wellman 1962;Goldman 1963). While investigating the biology of some of these lakes, Armitagc and House (1962) discovered that Lakes Bonney and Vanda had unusual and contrasting thermal fcaturcs.…”
Section: Introductionmentioning
confidence: 99%
“…Oxygen and carbon isotopic ratios were determined by standard procedures using a Nuclides Analysis Associates 6-60 double collector, double inlet mass spectrometer. Many writers have speculated on the history of Lake Bonney (Armitage & House 1962;Angino & Armitage 1963;Angino et al 1964;Hoare et al 1964;Shirtcliffe 1964;Shirtcliffe & Benseman 1964;House et al 1966;Boswell et al 1967). It has been suggested that the salts represent trapped sea water which has been somewhat modified by later processes of evaporation, addition of ions from surrounding soils and warm spring water, and the precipitation of CaS0 4, CaC0 3, and Na 2S0 4 (Angino et al 1964).…”
Section: Introductionmentioning
confidence: 99%
“…1959 . Angino and Armitage ( 1963 ) have published detailed chemical d a ta fo r Lake Vanda (Wilson and W ellma n , 1962 , fi g. I). They show that the upper 180 ft. (55 m. ) are essentially potable with less than 1,000 p .p.m.…”
Section: ~:J: ;mentioning
confidence: 99%